Perinatal foundations of personality pathology from a dynamical systems perspective. (February 2021) - Kaliush, Parisa R.; Gao, Mengyu (Miranda); Vlisides-Henry, Robert D.; Thomas, Leah R.; Butner, Jonathan E.; Conradt, Elisabeth; Crowell, Sheila E.
Abstract: The development of personality pathology is an interactive process between biologically based susceptibilities, interpersonal patterns, and contextual factors across the lifespan. In this paper, we argue that these interactions begin before birth. We describe the perinatal period (i.e. pregnancy and up to one year postpartum) as a sensitive developmental window during which regulatory and stress response systems that confer risk for personality pathology begin forming. In addition, we present converging evidence for significant associations between perinatal factors and later life personality disorders. Finally, we present this perinatal perspective through the lens of dynamical systems theory and emphasize the promise of this framework for guiding future personality disorder research, prevention, and intervention. Highlights: Interactive processes that confer risk for personality pathology begin before birth. Dynamical systems theory advances conceptualization of personality development. Future personality research should apply a dynamical systems perspective to the perinatal period. Perinatal healthcare is key for preventing later-life personality disorders.